Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Seventh Annual ACM/IEEE International Conference on Human-Robot Interaction 2012
DOI: 10.1145/2157689.2157811
|View full text |Cite
|
Sign up to set email alerts
|

Modelling empathic behaviour in a robotic game companion for children

Abstract: The idea of autonomous social robots capable of assisting us in our daily lives is becoming more real every day. However, there are still many open issues regarding the social capabilities that those robots should have in order to make daily interactions with humans more natural. For example, the role of affective interactions is still unclear. This paper presents an ethnographic study conducted in an elementary school where 40 children interacted with a social robot capable of recognising and responding empat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 29 publications
2
69
0
3
Order By: Relevance
“…For example, emotional pose recognition with the Nao robot is consistent (Beck, Canamero, & Bard, 2010), facilitating the use of emotional expression as a feedback channel that can be employed by the robot. Following from this general competence, it has been shown that an empathic or supportive robot is prefered to a non-affective agent by children, and that its use can possibly lead to increased performance, in both teaching scenarios (Saerbeck, Schut, Bartneck, & Janse, 2010), and peer-peer interactions (Leite, Castellano, Pereira, Martinho, & Paiva, 2012). Thus, what we see is that there are a range of physical and behavioural competencies, typically inspired directly by human behaviour, that are employed to make robot behaviour more naturalistic within a child-robot interaction context.…”
Section: Introductionmentioning
confidence: 99%
“…For example, emotional pose recognition with the Nao robot is consistent (Beck, Canamero, & Bard, 2010), facilitating the use of emotional expression as a feedback channel that can be employed by the robot. Following from this general competence, it has been shown that an empathic or supportive robot is prefered to a non-affective agent by children, and that its use can possibly lead to increased performance, in both teaching scenarios (Saerbeck, Schut, Bartneck, & Janse, 2010), and peer-peer interactions (Leite, Castellano, Pereira, Martinho, & Paiva, 2012). Thus, what we see is that there are a range of physical and behavioural competencies, typically inspired directly by human behaviour, that are employed to make robot behaviour more naturalistic within a child-robot interaction context.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary evaluation also suggested that the emotional behavior of the robot improved children's perception of the game. In another study [33], this robot responded empathically to children's affective states. Results suggest that the robot's empathic behaviors enhance children's attitude towards the robot.…”
Section: Related Workmentioning
confidence: 96%
“…The empathic model includes an a!ect detector that allows the robot to infer the valence of the feeling experienced by the children. The a!ect detector, based on Support Vector Machines (SVMs), processes in real-time behavioural and contextual features, providing as output a probability value for each of the following valence conditions: positive, neutral and negative [39].…”
Section: Paper Icts For Assessment and Intervention On Cultivation Ofmentioning
confidence: 99%